Model Bisnis Tanaman Florikultura Anggrek Pada Asosiasi Komoditas Anggrek Kabupaten Jombang - Istiyowati, Nuning; Sumarji, Sumarji; Mulyaningtiyas, Ratna Dewi (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
Orchid is a type of floriculture plant that attracts attention due to its high economic value compared to other horticultural products. However, this potential has not been matched by government attention to the floriculture subsector, which focuses on food crop commodities. Therefore, the Agriculture Office of Jombang Regency is attempting to fulfill its role in implementing policies that support local agriculture through the Orchid Commodity Association, which assists orchid farmers and is expected to increase the overall business potential. This research aims to (1) map the canvas business model that is being run by the Orchid Commodity Association of Jombang Regency, (2) identify the internal and external environment, strengths, weaknesses, threats, and opportunities of the orchid floriculture business in Jombang Regency, (3) determine the feasibility of orchid floriculture farming in Jombang Regency, and (4) compile an ideal design of orchid floriculture business in Jombang Regency. This research employed a qualitative methodology with narrative data presentation and analysis. Jombang Regency was selected as the research location because it has a farmer organization under the Orchid Commodity Association engaged in the orchid floriculture business. Data were gathered through interviews, field observation, and documentation. Data analysis employed qualitative analysis, business model canvas analysis, SWOT analysis, cost, revenue, and income analysis, and business model canvas analysis. The results of this study are as follows: (1) The nine elements in the Canvas Business Model regarding the business of the Jombang Regency orchid commodity association were obtained through in-depth interviews with internal respondents from the management and members. These elements provide an explanation and description of the business model being run; (2) The key success factors in determining the SWOT strategy are as follows: The factors that determine the SWOT strategy include the following: Having experts in cultivation and tissue culture is a strength, The limited area of greenhouse land is a weakness, Joint ventures with professional legal entities and partner plasma farmers are opportunities, The limited area of land to establish greenhouses is a threat. The optimal strategy is one that is both aggressive and expansionary. The Orchid Commodity Association of Jombang Regency has identified several strengths that can be leveraged to capitalize on existing opportunities and overcome challenges in the orchid business; (3) A revenue analysis of Dendrobium orchid farming, from seedling enlargement to adult flowering, indicates that revenue (R) is greater than cost (C). This condition is referred to as profit (R > C). The analysis of business efficiency yielded a ratio of revenue to cost (R/C) of 3.012. This ratio is greater than 1, indicating that the farm is profitable and efficient. This suggests that orchid farming in Jombang Regency is a viable enterprise; (4) The objective of redesigning the Business Model Canvas is to describe the optimal business development model, which is achieved by maximizing strengths, utilizing opportunities, and reducing weaknesses and threats, in accordance with the results of the SWOT analysis conducted previously. The development of this model is carried out by expanding consumer reach through optimizing digital marketing